Synthesis and Antimicrobial Activities of Indole-based Schiff Bases and their Metal Complexes: A Review - Priya, Bhanu; Utreja, Divya; Sharma, Shivali; Kaur, Gurbir; Madhvi (Current Organic Chemistry, 2023)
Heterocyclic compounds containing nitrogen have emerged as crucial entities in the realm of medicinal chemistry. Among these, Schiff bases derived from indole or compounds incorporating an indole moiety have demonstrated a wide range of biological properties, including antibacterial, anticancer, antitumor and antimicrobial activities. The diverse characteristics exhibited by Schiff bases have stimulated the exploration of their antimicrobial potential, with the aim of developing more effective drugs to save precious lives. This review article focuses on the synthesis of various Schiff bases derived from the indole moiety and their antimicrobial activities. The extensive body of work in synthesizing these Schiff bases and evaluating their antimicrobial properties is comprehensively discussed. The insights provided in this review can serve as a valuable resource for researchers engaged in the development of efficient drugs.
Keywords: heterocyclic compounds